Shrimp Plasma MANF Works as an Invertebrate Anti-Inflammatory Factor via a Conserved Receptor Tyrosine Phosphatase - Luo, Kaiwen; Chen, Yaohui; Wang, Fan (The Journal of immunology (1950), 2022)
For a long time, how anti-inflammatory factors evolved was largely unknown. In this study, we chose a marine invertebrate, , as a model and identified that shrimp mesencephalic astrocyte-derived neurotrophic factor (MANF) was an LPS-induced plasma protein, which exerted its anti-inflammatory roles on shrimp hemocytes by suppressing ERK phosphorylation and Dorsal expression. In addition, we demonstrated that shrimp MANF could be associated with a receptor protein tyrosine phosphatase (RPTP) to mediate negative regulation of ERK activation and Dorsal expression. More interestingly, shrimp RPTP-S overexpression in 293T cells could switch shrimp and human MANF-mediated ERK pathway activation to inhibition. In general, our results indicate that this conserved RPTP is the key component for extracellular MANF-mediated ERK pathway inhibition, which gives a possible explanation about why this neurotropic factor could both protect neuron cells from apoptosis and inhibit immune cell M1 activation in various species.